Parallel Visions : Modern Artists and Outsider Art - Tuchman, Maurice; Williams, Jonathan; Eliel, Carol S.; Freeman, Barbara; Heller, Reinhold; Cardinal, Roger; Wilson, Sarah; Bowman, Russel; Gisbourne, Mark; Gilman, Sander L.; MacGregor, John M.; Weiss, Allen S.; et al. (Los Angeles : County Museum of Art, 1992)
Corbaz, Aloïse ; Amenoff, Gregory ; Appel, Karel ; Artaud, Antonin ; Baechler, Donald ; Baselitz, Georg ; Bellmer, Hans ; Boltanski, Christian ; Borofsky, Jonathan ; Brauner, Victor et al.
Parallel Visions Modern Artists and Outsider Art, Los Angeles County Museum of Art, Los Angeles, October 18, 1992 - January 3, 1993 / Museo Nacional Reina Sofia, Madrid, February 11 - May 9, 1993 / Kunsthalle Basel, Basel, July 4 - August 29, 1993 / Setagaya Art Museum, Tokyo, September 30 - December 12, 1993
kunstcatalogus